2014
DOI: 10.1097/ijg.0b013e3182741afc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Nerve Fiber Layer Thickness Measurements for Glaucoma Detection

Abstract: GDx ECC and RTVue show a very good diagnostic ability to detect glaucoma. Most of the RNFL parameters had high AUCs and sensitivities. The diagnostic validity of GCC was comparable with that of the RNFL parameters, and they may be very useful in detecting RNFL damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Comparison of healthy subjects with OHT patients was not statistically significant as reported in earlier studies. [ 6 7 8 ] Comparisons for OR parameters were significant only when comparing healthy controls with PPG and EG patients. This finding agrees with other studies suggesting that OR parameters are affected less during the course of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of healthy subjects with OHT patients was not statistically significant as reported in earlier studies. [ 6 7 8 ] Comparisons for OR parameters were significant only when comparing healthy controls with PPG and EG patients. This finding agrees with other studies suggesting that OR parameters are affected less during the course of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, GCC parameters showed similar diagnostic ability with RNFL parameters. [ 8 13 14 15 16 17 18 19 ] Moreno et al . [ 20 ] reported that GCC parameters have slightly superior ability to discriminate between eyes with EG and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of our small number of glaucomatous eyes, diagnostic accuracies of the examinations were lower than in many studies where the proportion of glaucomatous eyes has been higher and classification has been predefined by VF and ONH findings (14,16,22,(28)(29)(30). In our study, as in others (32), the tests disagreed in classifying eyes as glaucomatous and healthy.…”
Section: Discussionmentioning
confidence: 71%
“…In all studies testing diagnostic accuracy, results depend on the reference. In many of those studies, nearly half the patients had glaucoma, and half have been healthy (14,16,22,(28)(29)(30). This is uncommon in real life.…”
Section: Discussionmentioning
confidence: 99%